Structural changes of tissue samples exposed to low frequency electromagnetic field: A FT-IR absorbance study. Issue 4 (2004) - Crupi Crupi, V. V.; Interdonato Interdonato, S. S.; Majolino Majolino, D. D.; Mondello Mondello, M. R. M. R.; Pergolizzi Pergolizzi, S. S.; Venuti Venuti, V. V.
Abstract : In the present work, we report on a preliminary Fourier Transform Infrared (FT-IR) Absorbance study performed on different kind of rat tissues, such as kidney and heart, exposed to a "non-ionizing" radiation source at low frequency, in the range typical of micro-waves (300 MHz < v < 300 GHz). The data were collected in a wide wavenumber region, from 400 cm −1 to 4000 cm −1 . The comparison of the absorbance spectra in the case of the normal tissues with the irradiated ones has shown significant differences in the spectral features in accordance with the morphological analysis performed by the optical microscopy.